Assessment of quality of life and its determinants among caregivers of lung cancer patients: a cross sectional study in a tertiary care centre of Kolkata, West Bengal, India - Pal, Jayita; Santra, Avradip (International Journal of Research in Medical Sciences, 2019)
Background: Lung cancer is the commonest cancer worldwide considering its incidence and mortality. It not only affects the life of the patient, but also has significant impact on the life of the primary caregivers too. The study aimed to assess the Quality of Life (QOL) among caregivers of lung cancer patients and to find out its determinants. Methods: It was an institution based cross-sectional study conducted in a tertiary care center of Kolkata with the help of a predesigned, pretested, structured, standardized questionnaire where 210 patient-caregiver dyads were included by complete enumeration method to assess quality of life of the caregivers and its possible predictors. Results: Half of the caregivers experienced poor quality of life (overall QOL score ≤ median score) as assessed by QOLLTI-F (Quality of Life in Life-Threatening Illness-Family Carer Version). Multivariate analyses suggested that gender, religion, area of residence, financial burden, stage and type of lung carcinoma, disability and depression among the patients were important determinants of quality of life of the caregivers. Conclusions: Comprehensive care covering different domains like financial risk protection, psycho-social assistance through governmental and also different non-governmental initiatives, self-help groups are the needs of the hour to address this important public health issue as caregiver’s life is equally important as that of the patient and they are highly interdependent.